Biomechanical validation of structural optimized patient-specific mandibular reconstruction plate orienting additive manufacturing. (September 2022) - Zhong, Shengping; Shi, Qimin; Van Dessel, Jeroen; Gu, Yifei; Sun, Yi; Yang, Shoufeng; ,
Highlight: Two structural optimized patient-specific mandibular reconstruction plates were designed to enhance the mandibular reconstruction. Biomechanical behavior of the patient-specific mandibular reconstruction plates was analyzed by finite element analysis. The generally customized reconstruction plate presented superior biomechanical performance than the personalized reconstruction plate with tangent arc upper margin. Abstract: Background and objective: Owing to the unexpected in vivo fracture failure of the original design, structural optimized patient-specific mandibular reconstruction plates (PSMRPs) were created to boost the biomechanical performance of bridging segmental bony defect in the mandibular reconstruction after tumor resection. This work aimed to validate the biomechanical benefit of the structural optimized PSMRPs relative to the original design and compare the biomechanical performance between PSMRP1 with generic contour customization and PSMRP2 with a tangent arc upper margin in mandibular angle region. Methods: Finite Element Analysis (FEA) was used to evaluate the biomechanical behavior of mandibular reconstruction assemblies (MRAs) concerning these two structural optimized PSMRPs by simulating momentary left group clenching and incisal clenching tasks. Bonded contact was set between mandibular bone and fixation screws and between PSMRP and fixation screws in the MRA, while the frictionless connection was allocated between mandibular bone and PSMRP. The loads were applied on four principal muscles, including masseter, temporalis, lateral and medial pterygoid, whose magnitudes along the three orthogonal directions. The mandibular condyles were retrained in all three directions, and either the left molars or incisors area were restrained from moving vertically. Results: The peak von Mises stresses of structural optimized PSMRPs (264 MPa, 296 MPa) were way lower than that of the initial PSMRP design (393 MPa), with 33 and 25% reduction during left group clenching. The peak magnitude of von Mises stress, minimum principal stress, and maximum principal strain of PSMRP1 (264 MPa, 254 MPa; -297 MPa, -285 MPa; 0.0020, 0.0020) was lower than that of PSMRP2 (296 MPa, 286 MPa; -319 MPa, -306 MPa; 0.0022, 0.0020), while the peak maximum principal stress of PSMRP1 (275 MPa, 257 MPa) was higher than that of PSMRP2 (254 MPa, 235 MPa) during both left group clenching and incisal clenching tasks. Conclusions: The structural optimized PSMRPs reveal their biomechanical advantage compared with the original design. The PSMRP1 presents better biomechanical performance to the patient-specific mandibular reconstruction than PSMRP2 as a result of its superior safety, preferable flexibility, and comparable stability. The PSMRP2 provides biomechanical benefit in reducing the maximum tension than PSMRP1, indicated by lower peak maximum principal stress, through tangent arc upper margin in mandibular angle region.